CHARACTERISTICS OF MYCOBACTERIUM TUBERCULOSIS POPULATION IN KARELIYA REPUBLIC - A. A. Vyazovaya; N. S. Solovieva; T. V. Sunchalina; I. V. Mokrousov; V. Yu. Zhuravlev; O. V. Narvskaya (Туберкулез и болезни лёгких)
Goal of the study: genotyping of Mycobacterium tuberculosis strains isolated from pulmonary tuberculosis patients in Kareliya Republic from June 2013 to January 2014.Results. Spoligotyping of 78 M. tuberculosis strains showed that they belonged to families of Beijing (n = 43), T (n = 11), URAL (n = 10), LAM (n = 8), Haarlem and Х. Eight out of 24 spoligotypes: SIT1 (Beijing); SIT40, SIT52, SIT53 (T); SIT35 и SIT262 (H3/URAL); SIT42 (LAM); SIT50 (Haarlem) were represented by two and more strains. The association between primary multiple resistance and Beijing genotype ofthe mycobacterium was defined, and 43.8% of M. tuberculosis strains of this genotype belonged to В0/W148 cluster which was of the epidemiological and clinical significance. T group was represented by drug susceptible strains only.